Priorities in health - Jamison, Dean T.; Disease Control Priorities Project (Washington, D.C. : World Bank, 2006)
This book covers new ground by examining important, complex areas, such as the delivery, management, and financing of health care and health research.
Col. maps on lining papers.
"Disease Control Priorities Project"--Cover.
"Companion volume to Disease control priorities in developing countries, 2nd ed. (DCP2)"--P. [4] of cover.
Includes bibliographical references (p. 183-186) and index.
aug 30/05/13
Loans
Keywords: Public health -- Developing countries; Medicine, Preventive -- Developing countries; Health planning -- Developing countries; Communicable Disease Control; Developing Countries; Health Planning; Preventive Medicine; Public Health